Reflections on “place attachment”: perceptions of urban redevelopment in an informal neighborhood in Istanbul - Inal-Çekiç, Tuba; Kozaman Aygün, Senem; Bilen, Ömer (Springer Science and Business Media B.V., 2024)
In the last two decades, urban redevelopment practices in informal settlements in Turkey often neglected inhabitants' spatial practices. The contradictions between conceived and lived space constitutes reactions to these spatial interventions. Against this background, this paper examines the association between place attachment and residents' attitudes toward the redevelopment project in an informally developed neighborhood. Using path and decision tree analysis of survey data, the paper explores the relationship between their attitudes towards and their attachment to the neighborhood. Our findings reveal that individuals' social and physical bonds with their neighborhood shape their attitude toward urban redevelopment. As such, this study confirms the idea that daily interactions between residents reinforce their place attachment in informal settlements where place identity compensates for the (low) quality of life. Still, our findings also demonstrate that residents' identification with the place is a more influential factor, compared to the risk of leaving the neighborhood, on the level of concern against spatial interventions. © The Author(s) 2023.
Keywords: Decision tree analysis; Informal settlement; Istanbul; Path analysis; Place attachment; Place identity